1998
DOI: 10.1002/(sici)1097-4644(19980401)69:1<44::aid-jcb5>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Genistein inhibits proliferation similarly in estrogen receptor-positive and negative human breast carcinoma cell lines characterized by P21WAF1/CIP1 induction, G2/M arrest, and apoptosis

Abstract: Genistein has been proposed to be responsible for lowering the rate of breast cancer in Asian women but the mechanism for this chemopreventive effect in vivo is unknown. In this study, we present in vitro evidence that genistein inhibits cell proliferation similarly in ER-positive and ER-negative human breast carcinoma cell lines. This inhibition is associated with specific G2/M arrest and induction of p21WAF1/CIP1 expression. Genistein results in a five-to six-fold increase in p21WAF1/CIP1 mRNA levels and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(69 citation statements)
references
References 21 publications
(32 reference statements)
4
62
0
3
Order By: Relevance
“…S1), 3 respectively, and are comparable with reported IC 50 values in this cell line (9, 11 -13 concentrations did not change cell viability after 48 h (data not shown), in agreement with other reports (2,14,19). Cells in passages 10 to 16 growing in the presence of phytochemicals or DMSO, as control, were used for analyses.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…S1), 3 respectively, and are comparable with reported IC 50 values in this cell line (9, 11 -13 concentrations did not change cell viability after 48 h (data not shown), in agreement with other reports (2,14,19). Cells in passages 10 to 16 growing in the presence of phytochemicals or DMSO, as control, were used for analyses.…”
Section: Resultssupporting
confidence: 90%
“…The number of cells from each treatment was estimated as a percentage of the number in the DMSO control. The number of cell generations (g) was counted according to the formula g = ln 2 (N/N 0 ), where N is the final number of cells. The time of growth comprises the sum of the time for initial adhesion (considered here to be 5 h), the time of complete division cycles (p  g), and a part of the unfinished last cycle (=p/2 on average), where p is one cell cycle duration.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…However, several earlier studies indicated that the tyrosine kinase was not required for the inhibitory eect of genistein on tumour growth (Barnes & Peterson, 1995;Stevens et al, 1994;Shao et al, 1998), nor for biochanin A and daidzein. Other mechanisms have been Figure 5 Eects of resveratrol, genistein and quercetin on porcine cerebral cortex Na + /K + -ATPase.…”
Section: Discussionmentioning
confidence: 96%
“…In 2008, over 12 million new cancer cases were diagnosed worldwide, breast cancer being one of the most frequently diagnosed in women, and the one characterized with the highest mortality rate [10]. However, a large body of data exists on the influence of polyphenols of plant origin on breast cancer [11][12][13][14]. For instance, an extract from the fruit of Terminalia chebula Retz.…”
Section: Introductionmentioning
confidence: 99%